3.140. Rozwiąż graficznie nierówność: a) x ^ 2 – 6x + 9 <= - x + 5 d) x - 8 < x ^ 2 + x - 6 b - x ^ 2 - 1 < - x - 3 c) (2 - x)(x + 3) <= 0; 25x ^ 2 > 4(5x – 1) f) b) (2 – 8x)(x + 1) > (1 – 4x)(x + 2) d) (2 – 6x)(3x + 9) >= x ^ 2 – 9 f) (2x – 3) ^ 2 < (x - 1, 5) ^ 2 b) - 2x ^ 2 + 5(x + 1) < 2(x + 2) - 3x * (x - 1) d) 8(x - 2) - x(x - 2) >= – 16 f) 1 – 2x * (x – 3) < x(5 - 4x) b) (2x - 3) ^ 2 > (x + 2) ^ 2 d) (2x – 1)(5x + 3) + 13 <= (3x - 1) ^ 2 + x f) 2(x - 4) * (x + 4) > 3x * (2x + 3) c) x ^ 2 + 2x – 3 >= – 2x – 3 e) x ^ 2 + 2x – 3 <= 1/5 * (x - 1) ^ 2 1) 1/9 * x * (6 - x) < (x - 3) ^ 2 + 1

3.140. Rozwiąż graficznie nierówność: a) x ^ 2 – 6x + 9 <= – x + 5 d) x – 8 < x ^ 2 + x – 6 b – x ^ 2 – 1 < – x – 3 c) (2 – x)(x + 3) <= 0; 25x ^ 2 > 4(5x – 1) f) b) (2 – 8x)(x + 1) > (1 – 4x)(x + 2) d) (2 – 6x)(3x + 9) >= x ^ 2 – 9 f) (2x – 3) ^ 2 < (x – 1, 5) ^ 2 b) – 2x ^ 2 + 5(x + 1) < 2(x + 2) – 3x * (x – 1) d) 8(x – 2) – x(x – 2) >= – 16 f) 1 – 2x * (x – 3) < x(5 – 4x) b) (2x – 3) ^ 2 > (x + 2) ^ 2 d) (2x – 1)(5x + 3) + 13 <= (3x – 1) ^ 2 + x f) 2(x – 4) * (x + 4) > 3x * (2x + 3) c) x ^ 2 + 2x – 3 >= – 2x – 3 e) x ^ 2 + 2x – 3 <= 1/5 * (x – 1) ^ 2 1) 1/9 * x * (6 – x) < (x – 3) ^ 2 + 1